Copper-promoted C5-selective bromination of 8-aminoquinoline amides with alkyl bromides - Shao, Changdong; Ma, Chen; Li, Li; Liu, Jingyi; Shen, Yanan; Chen, Chen; Yang, Qionglin; Xu, Tianyi; Hu, Zhengsong; Kan, Yuhe; Zhang, Tingting (Beilstein Journal of Organic Chemistry, 2024)
An efficient and practical method for the synthesis of C5-brominated 8-aminoquinoline amides via a copper-promoted selective bromination of 8-aminoquinoline amides with alkyl bromides was developed. The reaction proceeds smoothly in dimethyl sulfoxide (DMSO) under air, employing activated and unactivated alkyl bromides as the halogenation reagents without additional external oxidants. This method features outstanding site selectivity, broad substrate scope, and excellent yields.
Keywords: aminoquinolines; C–H bromination; copper catalysis; regioselectivity